Cytokinin oxidase/dehydrogenase OsCKX11 coordinates source and sink relationship in rice by simultaneous regulation of leaf senescence and grain number - Zhang, Wei; Peng, Kaixuan; Cui, Fubin; Wang, Dongling; Zhao, Jiangzhe; Zhang, Yanjun; Yu, Ningning; Wang, Yuyang; Zeng, Dali; Wang, Yonghong; Cheng, Zhukuan; Zhang, Kewei (Plant biotechnology journal, 2021)
Summary The flag leaf and grain belong to the source and sink, respectively, of cereals, and both have a bearing on final yield. Premature leaf senescence significantly reduces the photosynthetic rate and severely lowers crop yield. Cytokinins play important roles in leaf senescence and determine grain number. Here, we characterized the roles of the rice (Oryza sativa L.) cytokinin oxidase/dehydrogenase OsCKX11 in delaying leaf senescence, increasing grain number, and coordinately regulating source and sink. OsCKX11 was predominantly expressed in the roots, leaves, and panicles and was strongly induced by abscisic acid and leaf senescence. Recombinant OsCKX11 protein catalysed the degradation of various types of cytokinins but showed preference for trans‐zeatin and cis‐zeatin. Cytokinin levels were significantly increased in the flag leaves of osckx11 mutant compared to those of the wild type (WT). In the osckx11 mutant, the ABA‐biosynthesizing genes were down‐regulated and the ABA‐degrading genes were up‐regulated, thereby reducing the ABA levels relative to the WT. Thus, OsCKX11 functions antagonistically between cytokinins and ABA in leaf senescence. Moreover, osckx11 presented with significantly increased branch, tiller, and grain number compared with the WT. Collectively, our findings reveal that OsCKX11 simultaneously regulates photosynthesis and grain number, which may provide new insights into leaf senescence and crop molecular breeding.